Colaboração crítica na formação de coordenador: uma prática em construção - Santos, Rosemeire Rodrigues dos (2013)
The aim of this research is to investigate the developmental process of a pedagogical coordinator focused at the critical reflection of his actions in the conduction of teachers development sessions. Specifically, it critically investigates the relationship built between the researcher and the coordinator and how this bond allowed, or not, changes in the understanding of each other as far as teacher development is concerned, as well as in the modes of action of the coordinator in the Especial Project of Action (PEA). The study was conducted with the pedagogical coordinator of a public school in the city of São Paulo. Theoretically, it is based on the discussions of Vygotsky (1930, 1934), Leontiev (1978) about the Social Historical Cultural Activity Theory and the contributions of Engeström (2008, 2009, 2011), Magalhães (2010, 2011) e Liberali (2009a, 2011). The development of the pedagogical coordinator is understood as an Activity, in which coordinator and researcher are active participants in the production of knowledge. The critical collaborative research (PCCol), as discussed by Magalhães and the LACE group, supports the methodology of this research, which is targeted at critical collaborative relations between the participants. In other words, it is a study in which (a) theory and practiced are inseparable and (b) the argumentation organizes the collaborative production of knowledge in order to produce change. Three reflexive sessions were selected for the discussion of results. Data was analyzed with emphasis on the enunciative, discursive and linguistic aspects, considering the (1) theme, (2) contents, (3) turns, (4) types of questions, (5) lexical choices, following categories developed by Bronckart (1997/2007), Kerbrat-Orecchioni (1996/2006), Brookfield & Preskill (2005), Orsolini (2005), Pontecorvo (2005), Smyth (1992), Magalhães (2004, 2011) e Liberali (2004, 2011a, b, c). The results reveal that (i) the relations built between the participants were important in the sense that both could think critically about their ways of organizing and conducting the development of educators and (ii) this relation allowed the coordinator to change his ways of acting in the conduction of developmental sessions with teachers in the PEA, as well as it allowed the researcher to reflect about her discourse in the relation with the coordinator